Pengaruh Earning Per Share (EPS), Debt To Equity Ratio (DER) Dan Price Book Value (PBV) Terhadap Harga Saham Pada Perusahaan Food And Baverage Yang Terdaftar Di BEI - Umi Haniatul Faridah; Achmad Agus Priyono; Arini Fitria Mustapita (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThe purpose of this study was to analyze the effect of EPS, DER and PBV on Stock Prices at Food and Baverage Companies Listed on the Indonesia Stock Exchange (BEI). The population in this research were 26 companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange in 2016-2019. The samples used were 12 Food and Baverage companies. The sampling technique used purposive sampling. Data analysis using multiple regression analysis. The conclusion is that (1) the simultaneous value of EPS, DER, PBV had a significant effect on stock prices. (2) The Partially the value of EPS has a positive and significant effect on stock prices. (3) the partially value of the DER has no and insignificant effect on stock prices. (4) the partially value of the PBV has no and insignificant effect on stock prices.Keywords: EPS, DER and PBV, Stock Price